Non-Hfe iron overload: Is phlebotomy the answer? - Hazeldine, S.; Trinder, D.; Olynyk, John (Current Science, Inc, 2013)
Non-Hfe Iron Overload: Is Phlebotomy the Answer?Iron is an essential factor for life, however a physiologically optimal balance is critical. In this article we explore the role of iron as a co-factor in a range of chronic liver diseases and how it may contribute to the development of liver injury, fibrosis, cirrhosis and ultimately hepatocellular carcinoma. Whilst iron depletion therapy through phlebotomy is the most effective method of reducing iron stores, it is unclear whether this offers utility in the therapy of liver diseases in which iron is not the primary insult resulting in tissue injury. Here we examine the emerging evidence in the field of non-HFE hereditary haemochromatosis conditions associated with iron overload – is phlebotomy the answer?